Technology Adoption Among Small And Medium Enterprises (SME's): A Research Agenda - Thurasamy, Ramayah; Mohamad, Osman; Omar, Azizah; Marimuthu, Malliga (2009)
This paper presents the research agenda that has been proposed to develop an integrated model to explain technology adoption of SMEs in Malaysia.